174k views
2 votes
Find the polynomial. (2y − 9)(2y − 9) is the factored form of the expression .

User Kern Cheh
by
5.8k points

2 Answers

5 votes
(2y-9)(2y-9)
(2y-9)^2
(2y)^2-2*2y*9+9^2
4y^2-36y+81

User Koustuv Ganguly
by
5.8k points
0 votes

Answer:

The polynomial whose factored form is
(2y-9)(2y- 9)

is
4y^2+81-36y

Explanation:

Given : Factored form of a polynomial as
(2y-9)(2y- 9)

We have to find the polynomial whose factored form is
(2y-9)(2y- 9)

Consider the given expression
(2y-9)(2y- 9)


\mathrm{Apply\:exponent\:rule}:\quad \:a^b\cdot \:a^c=a^(b+c)

We have,


\left(2y-9\right)\left(2y-9\right)=\:\left(2y-9\right)^(1+1)=\:\left(2y-9\right)^2

Thus, Applying algebraic identity,
(a-b)^2=a^2+b^2-2ab, we have,

a = 2y and b = 9

Thus,
(2y-9)^2=(2y)^2+9^2-2\cdot 2y \cdot 9

Simplify, we have,


(2y-9)^2=4y^2+81-36y

Thus, The polynomial whose factored form is
(2y-9)(2y- 9)

is
4y^2+81-36y

User Florex
by
6.3k points